Pengaruh Kepercayaan, Persepsi Manfaat, Dan Persepsi Kemudahan Penggunaan Terhadap Minat Beli Kembali Produk Market Place Olx Pada Mahasiswa Universitas Negeri Padang - Deri Afrizal; Okki Trinanda (CV. ITTC INDONESIA, 2025)
This study aimed to determine the effect that trust, perceived benefits, and perceived ease of use have on the interest of students at Padang State University in repurchasing products from the OLX market place. The research in question is of the causal variety. Padang State University students constituted the population for the purpose of this study. The William Cochran formula served as the basis for determining the appropriate number of samples for the investigation. Through the use of the method of purposive sampling, a total of one hundred individuals were chosen. Primary data were used for this study, and they were collected by giving out questionnaires to students at Padang State University. The questions on the questionnaires were based on certain criteria that had been established beforehand. Multiple regression analysis carried out in SPSS 20 is the chosen approach to data interpretation. The findings indicate that (1) trust has a significant effect on repurchase interest in the OLX market place; (2) the perception of benefits has a significant effect on repurchase interest in the OLX market place; (3) the perceived ease of use has a significant effect on repurchase interest in the OLX market place; and (4) trust, perceived benefits, and perceived ease of use all have a significant effect on repurchase interest in products sold on the OLX market place.